Hot Potatoes Multimedia Applications in Evaluation of Indonesian Learning In SMP Students in Buru District - Susiati Susiati; Risman Iye; LOA Suherman (Hasanuddin University, 2019)
This study aims to find out wheter there is an influence of the Hot Potatoes multimedia application in evaluating junior high school students' learning outcomes in Indonesian language learning. The study design uses an evaluation model with the multimedia application Hot Potatoes. The method used is quantitative description and qualitative description, which is to show the effect of evaluating student learning outcomes and student and teacher responses to the effectiveness of the use of multimedia Hot Potatoes. The data source of this research is the IX grade junior high school students in Buru Regency. Data collection techniques used in this study are test techniques using the multimedia application Hot Potatoes in the form of a Multiple-Choice Test (multiple-choice). The results showed that the application of the Hot Potatoes multimedia application in evaluating the learning outcomes of junior high school students in Indonesian language learning had a major influence on quality learning. This can be seen from the results of the evaluation of 50 middle school students from cycle I, cycle II, and cycle III. The percentage of students completeness in cycle I was 60%, cycle II was 86%, and cycle III was 94%. Meanwhile, the percentage of students completeness in the first cycle was 40%, second cycle was 14%, and third cycle was 6%.